Effects of core strengthening and proprioceptive neuromuscular facilitation technique on the Barthel index and balance in patients with hemiplegic stroke –a quasi-experimental study - Yousaf, Qandeel; Rabiiya Noor; Ghafoor, Imran (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the effectiveness of core strengthening exercises and proprioceptive neuromuscular facilitation techniques on functional performance and balance among patients with haemiplegic stroke. Method: The quasi-experimental study was conducted from March to August 2021 at Imran Idrees Hospital, Sialkot, Pakistan, and comprised stroke patients of either gender who were divided into proprioceptive neuromuscular facilitation group A and core strengthening group B. In both groups, the treatment was given for 6 weeks with 5 30-minute sessions per week. Functional performance and balance were measured using Barthel Index and Berg Balance Scale. Data were collected at baseline, 3 weeks and 6 weeks. Data was analysed using SPSS 22. Results: Of the 48 patients, 24(50%) were in each of the 2 groups. There were 39(81.25%) male and 9(18.75%) female subjects with an overall mean age of 45±4.919 years. Mean Barthel Index score in group A was 62.50±7.22 at baseline and 74.79±7.14 after 6 weeks. Mean Berg Balance Score was 25.04±2.15 at baseline and 41.66±6.04 after 6 weeks (p<0.05). In group B, Barthel Index score was 61.45±6.33 at baseline and 80.83±7.61 after 6 weeks. Mean Berg Balance score was 25.33±3.38 at baseline and 47.08±5.99 after 6 weeks (p<0.05). There was a significant difference in group B scores compared to group A (p<0.01). Conclusion: Core strengthening programme was more effective than the proprioceptive neuromuscular facilitation programme in terms of activity of daily living and balance in patients with stroke. Keywords: Activity of daily living, Berg Balance Scale, Barthel Index, Core strengthening, Proprioceptive neuromuscular facilitation, Stroke.